Estimativa da erosividade das chuvas no alto sertão alagoano através de modelos matemáticos - Silva, Dyego Henrique Ferro (2023)
Erosivity is defined as the potential of rainfall to cause soil erosion and is a function exclusively of the physical characteristics of the rain itself, especially the quantity, intensity and diameter of the droplet, as well as the terminal velocity. The present study aimed at estimating rainfall erosivity based on pluviometric data in the micro-regions of Sertão do São Francisco and Serrana do Alto Sertão Alagoas, based on three mathematical models. The study area includes the territorial division of the State of Alagoas formed by the microregions Alagoana do Sertão do São Francisco (Delmiro Gouveia, Piranhas and Olho Dágua do Casado) and Serrana do Alto Sertão Alagoano (Água Branca, Canapi, Inhapi, Pariconha and Mata Grande). In this research rainfall information from 06 municipalities of Alto Sertão Alagoano was analyzed, in the period from 1913 to 1985. To estimate erosivity the models proposed by Lombardi Netto; Moldenhauer (1992); Morais et al. (1991); and Rufino et al. The rainfall was evaluated using classical statistics and the erosivity data were submitted to linear regression analysis using the Sisvar software. For the elaboration of the maps the Mapbiomas platform was used in partnership with Google Earth Engine. For the geomorphometric analyses SRTM images were used, made available by INPE via the TOPODATA platform, producing the MDE. For data manipulation and verification the Qgis software was used. Água Branca, within the Microregion Serrana do Alto Sertão Alagoas, obtained the highest average erosivity values and Canapi, the lowest. Within the Microregion Sertão do São Francisco, Piranhas stands out for presenting the lowest average erosivity values and Olho Dágua do Casado the highest. The average monthly precipitation for the counties that make up the Microregion Serrana do Alto Sertão Alagoano was approximately 82.81 mm for Água Branca, 51.97 mm for Mata Grande and 47.55 mm for Canapi. The average monthly precipitation for the municipalities that make up the Microregion of Sertão do São Francisco was approximately 42.49 mm for Delmiro Gouveia, 41.50 mm for Piranhas and 46.01 mm for Olho Dágua do Casado. The highest average monthly erosivity values were verified in the Microregion Serrana do Alto Sertão Alagoas, a region of higher altitudes, with predominantly gentle-rounded relief. The Microregion of Sertão do São Francisco, in Alagoas, presented the lowest erosivity and precipitation rates. The models presented a good correlation in all the municipalities that make up the region of the high sertão of Alagoas.